Employee Satisfaction Building Through Transformational Leadership and Organizational Culture - Tampubolon, Nurdin; Propheto, Arfendo (International Journal of Engineering and Technology, 2018)
ASEAN Economic Community / AEC has made the competition even more sharply and pooling of regional economy exposes the company in increasingly competitive, and dynamic. These conditions require companies to utilize all available resources in order not to lose out in the global competition. Human resources is one of the resources owned by the company among several other resources and a vital corporate assets that are expected to utilize all the potential available in the company. This research was conducted at PT Bangkitgiat Usaha Mandiri (PT BUM) is a company engaged in the cultivation and processing of palm crude palm oil (CPO) is located in the city of East Waringin Central Kalimantan. The company's performance is inseparable from how the business and what has been done by employees. Therefore, the company must seek a way in order to satisfy employee. Meanwhile, to satisfy the employees, the role of transformational leadership, organizational culture plays an important role. This Research wanted to know how the influence of the independent variable leadership, organizational culture on employee satisfaction as the dependent variable. This research will contribute in increasing employee satisfaction to the firm. This paper is still conceptual framework and will be continued to be a research proposal as part of the writing of a dissertation.Â